PENINGKATAN LITERASI NUMERASI SISWA SEKOLAH DASAR MELALUI METODE GASING: BELAJAR MATEMATIKA DENGAN FUN DAN INTERAKTIF (SD NEGERI 4 PAREPARE) - Aprizal Resky; Muhammad Rifki Nisardi; Zaitun; Hartina Husain; Kusnaeni; Andi Oxy Raihan M.R; Dwicky Herlambang; Dewi Citra Ramadhani (Universitas Mataram, 2025)
The low level of numeracy literacy among elementary school students in Indonesia poses a significant challenge in mathematics education, as reflected in the 2018 PISA results. This gap is exacerbated by conventional teaching methods that lack concrete media and interactive approaches, making it difficult for students to grasp fundamental concepts. Mathematics anxiety further undermines students’ motivation and learning outcomes. An enjoyable and communicative learning approach is therefore needed to enhance students’ understanding of numeracy concepts effectively and sustainably. This activity aimed to improve the numeracy literacy of fourth-grade students at SD Negeri 4 Parepare through the implementation of the interactive and engaging GASING method, which is easily applicable by teachers in the classroom. The program was carried out in three stages—preparation, implementation, and evaluation—involving 40 fourth-grade students. Activities such as Lari Balon (Balloon Run), Matematika Berantai (Chain Mathematics), and Mathematical Crosswords enhanced students’ motivation, concentration, and teamwork. Evaluation results indicated improved arithmetic skills and understanding of basic mathematical concepts. The Kartini group achieved the highest score with a total of 247 points. Feedback from teachers and students highlighted that the GASING method made learning more enjoyable, reduced mathematics anxiety, and encouraged active student participation. The GASING method proved effective in improving students’ numeracy literacy through a game-based, enjoyable learning approach and is suitable for implementation in other elementary schools.